42=6t

Simple and best practice solution for 42=6t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42=6t equation:


Simplifying
42 = 6t

Solving
42 = 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
42 + -6t = 6t + -6t

Combine like terms: 6t + -6t = 0
42 + -6t = 0

Add '-42' to each side of the equation.
42 + -42 + -6t = 0 + -42

Combine like terms: 42 + -42 = 0
0 + -6t = 0 + -42
-6t = 0 + -42

Combine like terms: 0 + -42 = -42
-6t = -42

Divide each side by '-6'.
t = 7

Simplifying
t = 7

See similar equations:

| 2x-8=x+7 | | Ln(4x-5)=0 | | 157.78=2.41w+14.23 | | -421=7(-4+7n)-1 | | Y=-3x-12+5 | | 12x+3=8x+7 | | -8p+9+9p=15 | | x^2+14x=900 | | 135+5=140-40 | | 0=x^2-14x+45 | | 5(2a-5b+3c)= | | d^2+12d+36= | | 7x-5=3x+10 | | -3-(-3x)=0 | | 3x+5=4x-40 | | -4-(-3x)=0 | | -2-(-3x)=0 | | 4w^2-28=0 | | y+12y=8 | | 0.2X+27=82 | | -1-(-3x)=0 | | -4(3x+3)=-4(5x-3) | | x+mx+b=0 | | 0=x^2+11x+18 | | 7x+12=0 | | 7c+3=13 | | 0=x^2-11x+18 | | 10x=6x-12 | | u^2-3u-28=0 | | x+3(-1)=0 | | (3x+3)(x+-2)=0 | | -5+x^2=0 |

Equations solver categories